Ekonomi Politik Media dalam Perspektif Komunikasi dan Sosial-Budaya - Imsar; Husaini, Ahmad (Ikatan Da'i Indonesia, 2023)
Harold Innis and Marshall McLuhan recognized the fact that technologies have a communicative dimension in and of themselves and play an important role in the formation of political economy. The economic field clearly cannot be separated from capitalism; and capitalism and industry are two things that cannot be tolerated. Furthermore, culture is one of the most interesting contents to be